Maquiladoras and market mamas: women's work and childcare in Guatemala City and Accra - Quisumbing, Agnes R.; Hallman, Kelly; Ruel, Marie T. (Informa UK Limited, 2007)
This paper analyses work, childcare, and earnings of mothers in the slums of Guatemala City and Accra. Similar factors affect decisions to work and to use formal daycare, but the importance of childcare varies with the role of the formal labour sector. In Guatemala, where formal sector work is important, higher prices for informal care increase formal daycare use. However, daycare prices and proximity to daycare centers do not significantly affect earnings in Guatemala City and Accra, respectively. Providing formal daycare may be more important to mothers' decision to work in cities where formal sector work dominates.